(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The Algerian navy was the height of its strength during the sixteenth and seventeenth centuries, Where Algeria was able to occupy a special position in the Mediterranean basin, and the political and administrative system during the era of the Dayaat many characteristics made the relationship between Algeria and the Ottoman Empire take other dimensions, where Algeria enjoyed great autonomy in its governance and dominion internally and externally. as for the relationship of the islands with the Moroccan and Arab countries, they ranged from peace and cooperation at times to violence, war, and conflict. As well as for European countries except Spain, which remained in permanent hostility and wars with Algeria until the late eighteenth century because of the Spanish control until 1792.